2014
DOI: 10.1248/bpb.b13-00619
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of <i>Rosa multiflora</i> Root Extract Improves Atopic Dermatitis-Like Skin Lesions Induced by Mite Antigen in NC/Nga Mice

Abstract: The roots of Rosa multiflora THUNB. (RM) has been used in oriental traditional medicines as remedies for scabies, rheumatic arthralgia and stomatitis which were practicably related with today's inflammatory and allergic diseases. In the present study, we evaluated whether RM root extract (RME) and its major constituent, 2-(3,4-dihydroxyphenyl)-6-(4-hydroxyphenyl)-8-(2,4-dihydroxyphenyl)-2,3-trans-6,7-cis-7,8-trans-3,4,7,8-tetrahydro-2H,6H-pyrano[2,3-f ] chromene-3,7,9-triol (RM-3) belongs to condensed tannins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Of the different components that can be found in Rosa multiflora roots, the most likely candidate to act against AD is the condensed tannin RM-3. RM-3 is the most abundant phytochemical in Rosa multiflora root extract, and Park et al [177] proved that this isolated tannin reproduced the effects previously observed for the whole extract.…”
Section: Rose Hip and Diseasementioning
confidence: 60%
See 1 more Smart Citation
“…Of the different components that can be found in Rosa multiflora roots, the most likely candidate to act against AD is the condensed tannin RM-3. RM-3 is the most abundant phytochemical in Rosa multiflora root extract, and Park et al [177] proved that this isolated tannin reproduced the effects previously observed for the whole extract.…”
Section: Rose Hip and Diseasementioning
confidence: 60%
“…Topical application of extracts from Rosa multiflora root extracts improved AD-like injury in mice [177]. Anti-AD activity of Rosa multiflora seems to be related to its anti-inflammatory properties, since application of extracts reduced mRNA levels of inflammatory mediators cyclooxygenase 2 (COX-2) and inducible Nitric Oxide Synthase (iNOS).…”
Section: Rose Hip and Diseasementioning
confidence: 99%
“…Hence, natural immune modulators from herbal extracts or derivatives may be useful for treating AD symptoms. Such modulators include 7,8,4’-trihydroxyisoflavone (a metabolite of soy daidzin), flavonoids from Averrhoa carambola L. [ 277 , 278 ], eriodictyol (also a flavonoid) from Acer mono and Eriodictyon californicum [ 279 ], and tannins from Rosa multiflora [ 280 ]. In their research on apigenin, Hou et al revealed that this compound facilitates epidermal permeability barrier by stimulating epidermal differentiation, lipid synthesis and secretion, as well as cutaneous antimicrobial peptide production [ 281 ].…”
Section: Skin Diseasesmentioning
confidence: 99%
“…It has strong antioxidant, anti-inflammatory, anticarcinogenic and antimutagenic activities [11]. In addition, the condensed tannin attenuates inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)2 expression in AD NC/Nga mouse model [12]. Another similar study reported that two condensed tannins effectively suppress Th2 cytokines in AD mice [13].…”
Section: Introductionmentioning
confidence: 98%